Maintenance Energy Requirements in Modern Broilers Fed Exogenous Enzymes - Caldas, J.V.; Hilton, K.M.; Boonsinchai, N.; Mullenix, G.; England, J.A.; Coon , C.N. (International Journal of Poultry Science, 2022)
Objective: The objective of this study was to determine if exogenous enzymes reduce the metabolizable energy requirements for maintenance in broilers. Materials and Methods: Two feeds were tested, a negative control and negative control plus enzyme composite. The composite was a proprietary blend of glucanase + xylanase + cellulase + arabinofuranosidase + protease + phytase. Feed allowances were 30-100% of the ad libitum feed intake from 16-27 days. The retained energy in the carcass was evaluated as protein gain, g×5.45 kcal g–1+fat gain×8.95 kcal g–1. A linear regression of Y = Retention energy kcal/kg0.70 was regressed by X = Metabolizable energy intake kcal/kg0.70 where the metabolizable energy intake at zero carcass retention energy was the metabolizable energy of maintenance. Results: Body weight gain was +6.39 g day–1 with the enzyme treatment at ad libitum intake. The metabolizable energy for maintenance was 168±4.2 kcal/kg0.70 (R2 = 0.98) for the enzyme treatment and 160±4.5 kcal/kg0.70 (R2 = 0.98) for the control (p